Is Khat chewing habit a risk factor for occlusal caries progression? - Al-Alimi, Khaled Rashad; Razak, Abdul Aziz Abdul; Saub, Roslan (Faculty of Medicine, Makerere University, 2018)
Backgrounds: People in Yemen and in East African countries chew khat more than five hours daily. Objectives: The aim of this study was to assess the relationship between khat and occlusal caries progression. Methods: A cohort study was carried out among 98 Yemeni khat chewers and 101 non-chewers aged 18-35 years old with early occlusal caries lesions. All participants answered questions on socio-demographic, khat , oral hygiene , sugar intake, and oral health knowledge at baseline. All posterior teeth with an early enamel lesion on occlusal surfaces detected by visual inspection at baseline were also subjected to DIAGNOdent assessment to confirm early lesion (DIAGNOdent reading 13-24). Participants were re-examined after 12 weeks. Caries progression was considered to occur when the DIAGNOdent reading was >25. Data were analyzed using Relative risk, Mann-Whitney U test, a Wilcoxon Signed-Rank test and logistic regression analysis. Results: Occlusal caries progression incidence between khat chewers and non-chewers, with the relative risk was 1.68. There was no significant difference in occlusal caries progression on chewing side and non-chewing side among khat chewers. Khat chewing was a statistical predictor for those with low income. Conclusion: Khat is a risk factor for occlusion caries progression among low income group.